Horizon Effects in Average Returns: The Role of Slow Information Diffusion - Boguth, Oliver; Carlson, Murray; Fisher, Adlai; Simutin, Mikhail (Review of Financial Studies, 2016)
We characterize linkages between average returns calculated at different horizons. Theoretically, when stocks incorporate information slowly, average short-horizon returns are downward biased. Buy-and-hold strategies can amplify the effect. In contrast, existing theories analyze price noises that are independent of fundamentals, and buy-and-hold portfolio returns are unaffected. We document horizon effects as large as 10% annualized in daily and monthly style portfolios and international indices. Slow reaction to market information, identified by gradually declining lagged betas, is an important cause. These findings have natural consequences for performance evaluation. Received July 2, 2012; accepted June 28, 2015 by Editor Andrew Karolyi.